Detection of peroxyl radicals from polluted air by free radical reaction combined with liquid chromatography signal amplification technique. Issue 9 (12th February 2018) - Wang, Guoying; Jia, Shiming; Niu, Xiuli; Liu, Yanrong; Tian, Haoqi; Chen, Xuefu; Shi, Gaofeng
Abstract: Free radicals play an important role in the oxidizing power of polluted air, the development of aging‐related diseases, the formation of ozone, and the production of secondary particulate matter. The high variability of peroxyl radical concentration has prevented the detection of possible trends or distributions in the concentration of free radicals. We present a new method, free radical reaction combined with liquid chromatography photodiode array detection, for identifying and quantifying peroxyl radicals in polluted air. Functionalized graphene was used for loading peroxyl radicals and reactive molecules in air sampling system, which can facilitate reaction kinetics (charge transfers) between peroxyl radicals and reaction molecules. Separation was performed with and without a preliminary exposure of the polluted air sample to reactive molecule(s) system. The integral chromatographic peak areas before and after air sampling are used to quantify the atmospheric peroxyl radicals in polluted air. The utility of the new technique was tested with measurements carried out in the field.